Palliative Management of Advanced Pancreatic Cancer: The Role of Gastroentero-hepatologist - Randy Adiwinata; Andrea Livina; Bradley Jimmy Waleleng; Nelly Tendean; Fandy Gosal; Luciana Rotty; Jeanne Winarta; Andrew Waleleng (Acta Medica Indonesiana)
Pancreatic cancer commonly diagnosed at late stage due to subtle clinical manifestation and associated with low 5-year survival rate. Only 10-20% of patients were found in resectable or localized stage. Several complications may arise due to advanced pancreatic cancer such as obstructive jaundice, gastric outlet obstruction, pancreatic cancer cachexia, pruritus of cholestasis, and cancer pain. Palliative management should be optimized in order to improve patient’s quality of life. A gastroentero-hepatologist should collaborate with other specialties to give comprehensive palliative care for advanced pancreatic cancer patients.